Management of chronic myelogenous leukemia with COVID-19 and hepatitis B - Yu, Tian; Li, Weiming; Yu, Tao (Frontiers in Oncology, 2023)
The application of immunosuppressive agents and targeted drugs has opened a novel approach for the treatment of hematological tumors, and the application of tyrosine kinase inhibitors for the treatment of chronic myeloid leukemia is one of the landmark breakthroughs that has considerably improved the prognosis of CML patients. However, with the extensive use of TKI, the co-infection of CML patients has become increasingly apparent, especially regarding infectious diseases such as hepatitis B and COVID-19. The underlying mechanism may be related to the inhibition of the immune function by TKI. Poor management, including disease progression due to the infectious disease or TKI dose reduction or discontinuation, may lead to adverse clinical outcomes and can even be life-threatening. Therefore, this review principally provides an overview of the pathogenesis and standardized management principles of CML patients with comorbid COVID-19 or hepatitis B in order to improve clinicians' awareness of the risks so as to more effectively diagnose and treat CML and improve the survival rate and quality of life of patients.